Anti-Inflammatory Potential of Combined Turmeric Rhizome Extract (Curcuma longa L.) and Hydroxyapatite in Male White Mice (Mus musculus) - Ahmad Hafizullah Ritonga; Fatma Amelia; Herlina Herlina; Barita Aritonang; Karnirius Harefa (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Inflammation is a protective response of the body to tissue injury that needs to be controlled to prevent further damage. The use of nonsteroidal anti-inflammatory drugs is effective; however, it has the potential to cause side effects, so safer alternatives are needed. Turmeric rhizome (Curcuma longa L.) is known to have anti-inflammatory activity, while hydroxyapatite (HA) is biocompatible and has the potential to enhance the effectiveness of the combination. This study aims to evaluate the anti-inflammatory potential of the combination of turmeric rhizome ethanolic extract and HA in male white mice (Mus musculus). This research method uses an experimental design with an acute inflammation model induced by intraplanar injection of 1% carrageenan. A total of 25 mice were divided into five groups: negative control (0.5% Na-CMC), positive control (diclofenac sodium), and three treatment groups at 0.5%, 1%, and 1.5%. Edema volume was measured every 1 hour for 6 hours and analyzed using the Kruskal-Wallis test followed by a post hoc test. The results of this study showed that all treatment groups exerted anti-inflammatory effects compared to the negative control, as indicated by decreases in edema volume and the percentage of inflammation and increases in the percentage of inhibition of inflammation, with the 1.5% concentration showing the most optimal effect. These findings indicate that the combination of turmeric rhizome ethanolic extract and HA has potential as an effective anti-inflammatory agent in male white mice.